Current Status and Perspectives for the Estimation of Crop Water Requirements from Earth Observation - Guido D’Urso (Italian Journal of Agronomy, 2010)
This paper presents an overview of current techniques and recent developments in the application of Earth Observation data for assessing crop water requirements. During recent years there has been much progress in understanding land surface-atmosphere processes and their parameterisation in the management of land and water resources. This knowledge can be combined with the potentiality of Earth Observation techniques from space, which are able to provide detailed information for monitoring agricultural systems. As today, two main developments in the field of Earth Observation data acquisition and analysis have occurred: a) availability of new generations of sensors, with enhanced spectral and spatial resolution; b) detailed knowledge of the processes that determine the response of land surface as detected from remote sensors in different regions of the electromagnetic spectrum. These advancements have made possible a “quantitative” approach in the interpretation of Earth Observation data, ready for being transferred to operative applications i.e. for irrigation scheduling and water management. This paper presents a review of current applications of optical data in the visible and near infrared spectral regions, with particular emphasis to the experiences developed by the author within AQUATER and other research projects project.